2021
DOI: 10.3389/fphar.2021.760674
|View full text |Cite
|
Sign up to set email alerts
|

New Insights Into the Anticonvulsant Effects of Essential Oil From Melissa officinalis L. (Lemon Balm)

Abstract: Melissa officinalis L. is used in traditional European and Iranian folk medicines to treat a plethora of neurological diseases including epilepsy. We utilized the in vitro and in vivo models of epilepsy to probe the anticonvulsant potentials of essential oil from M. officinalis (MO) to gain insight into the scientific basis for its applications in traditional medicine for the management of convulsive disorders. MO was evaluated for effects on maximal electroshock (MES) and pentylenetetrazole (PTZ) -induced sei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 94 publications
1
7
0
Order By: Relevance
“…In the pathogenesis of chronic epilepsy, a large number of superoxide anions can be produced, and the endogenous antioxidant enzymes SOD, GSH, GSR and cat are rapidly consumed, resulting in the production of a large number of toxic lipid peroxide increased and induced the oxidative stress. In addition, in PTZ-induced kindling in mice, it was found that reactive oxygen species was activated, and its production agrees with decrease in antioxidant related enzymes (Frantz et al 2017;Chindo et al 2021). In this study, we found that treated with GEAT decoction reduced MDA levels in PTZ-kindled mouse hippocampus, while increased CAT and SOD activities, as well as increased GSH levels when compared with that of PTZ-kindled mice.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In the pathogenesis of chronic epilepsy, a large number of superoxide anions can be produced, and the endogenous antioxidant enzymes SOD, GSH, GSR and cat are rapidly consumed, resulting in the production of a large number of toxic lipid peroxide increased and induced the oxidative stress. In addition, in PTZ-induced kindling in mice, it was found that reactive oxygen species was activated, and its production agrees with decrease in antioxidant related enzymes (Frantz et al 2017;Chindo et al 2021). In this study, we found that treated with GEAT decoction reduced MDA levels in PTZ-kindled mouse hippocampus, while increased CAT and SOD activities, as well as increased GSH levels when compared with that of PTZ-kindled mice.…”
Section: Discussionsupporting
confidence: 67%
“…Studies have found that epilepsy is also closely related to oxidative stress and mitochondrial dysfunction (Chindo et al 2021). The production of free radicals plays an important role in biological function regulation, cell structure damage and the pathogenesis of neurodegenerative diseases of the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…35 A recent study showed that the essential oil of M. officinalis reduces hippocampal neuron firing through the inhibition of the voltage-gated sodium channel. 36…”
Section: Resultsmentioning
confidence: 99%
“…35 A recent study showed that the essential oil of M. officinalis reduces hippocampal neuron firing through the inhibition of the voltage-gated sodium channel. 36 The occurrence of HLTE is often used as an endpoint for the quantification of PTZ-induced convulsions and is described when an angle of the hindlimbs to the torso exceeds 90°. 37 In the case of DZP-treated mice, as well as those from the controltreated and citronellal-treated groups, the occurrence of HLTE was postponed from the initial convulsion for almost double the time needed for convulsions to occur (Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…About 30-40% of the patients that received treatment experience numerous adverse effects associated with the current antiepileptic drugs (Zhul et al, 2014). Also, the current antiepileptic drugs are effective in only 30-40% of the patients, neither provide a cure for epilepsy nor prevent the progression of epilepsy disease (Doeser et al, 2015;Chindo et al, 2021). Thus, there is need for continuous search for safer and more efficacious antiepileptic agents that will improve the patients 'quality of life.…”
Section: Introductionmentioning
confidence: 99%